Pengaruh Motivasi Kerja dan Kepuasan Kerja terhadap Kinerja Pegawai PT Fasen Creative Quality - Wijaya, Ragil Sena; Siska, Elmira; Indra, Natal (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
This study aims to determine how much influence work motivation and job satisfaction have on the performance of PT Fasen Creative Quality employees. The research method used is a quantitative method approach with data collection techniques using non-probability sampling with a total sample of 39 employees. Data collection using a questionnaire with a Likert scale unit. Data analysis techniques include validity test, reliability test, classic assumption test, multiple linear regression test, t test, and f test. The results of this study indicate that partially work motivation has a positive effect on employee performance, job satisfaction has a positive effect on employee performance. Simultaneously, motivation and job satisfaction have a positive and significant effect on employee performance